The genus Nicostratus Distant from China (Hemiptera: Miridae: Deraeocorinae) - Xu, Jing-Yang; Liu, Guo-Qing (Zootaxa, 2007)
Two species are recognized, including a new species, Nicostratus frontmaculus, from Menghai, Yunnan Province, China. Photographs of the species and illustrations of genital structure are given, and distributional records of all species are provided. A key to the world species is provided. Type specimens of the new species are deposited in the Institute of Entomology, College of Life Sciences, Nankai University, Tianjin, China.